2017
DOI: 10.1093/gbe/evx061
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Genomic Approach to Understand the Basis of Host Adaptation in Achromobacter

Abstract: Over the past decade, there has been a rising interest in Achromobacter sp., an emerging opportunistic pathogen responsible for nosocomial and cystic fibrosis lung infections. Species of this genus are ubiquitous in the environment, can outcompete resident microbiota, and are resistant to commonly used disinfectants as well as antibiotics. Nevertheless, the Achromobacter genus suffers from difficulties in diagnosis, unresolved taxonomy and limited understanding of how it adapts to the cystic fibrosis lung, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 93 publications
(94 reference statements)
1
47
0
Order By: Relevance
“…We believe they should be used to validate the groupings obtained by the classical gANI cutoff-based species delimitation procedure (Goris et al, 2007;Konstantinidis and Tiedje, 2005;Richter and Rossello-Mora, 2009) that dominates current genotaxonomic research. It is well documented that pan-genome-based groupings tend to better reflect ecologically relevant phenotypic differences between groups (Caputo et al, 2015;Jeukens et al, 2017;Lukjancenko et al, 2010). We recommend that future geno-taxonomic studies search for a consensus of the complementary views of genomic diversity provided by OGRIs, core-and pan-genome phylogenies, as performed herein.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We believe they should be used to validate the groupings obtained by the classical gANI cutoff-based species delimitation procedure (Goris et al, 2007;Konstantinidis and Tiedje, 2005;Richter and Rossello-Mora, 2009) that dominates current genotaxonomic research. It is well documented that pan-genome-based groupings tend to better reflect ecologically relevant phenotypic differences between groups (Caputo et al, 2015;Jeukens et al, 2017;Lukjancenko et al, 2010). We recommend that future geno-taxonomic studies search for a consensus of the complementary views of genomic diversity provided by OGRIs, core-and pan-genome phylogenies, as performed herein.…”
Section: Discussionmentioning
confidence: 90%
“…The genomic analyses presented in this study for five Smc1 and Smc2 strains, respectively, fully support their 17 734 735 736 737 738 739 740 741 742 743 744 745 746 747 748 749 750 751 752 753 754 755 756 757 758 759 760 761 762 763 764 765 766 767 768 769 770 771 772 773 774 775 776 777 778 779 780 separate species status from a geno-taxonomic perspective. Given the recognized importance of gene gain and loss processes in bacterial speciation and ecological specialization (Caputo et al, 2015;Jeukens et al, 2017;Richards et al, 2014;Shapiro and Polz, 2015), as reported also in plants , we think that the evidence gained from pan-genome phylogenies is particularly informative for microbial geno-taxonomic investigations. We believe they should be used to validate the groupings obtained by the classical gANI cutoff-based species delimitation procedure (Goris et al, 2007;Konstantinidis and Tiedje, 2005;Richter and Rossello-Mora, 2009) that dominates current genotaxonomic research.…”
Section: Discussionmentioning
confidence: 91%
“…The genomic analyses presented in this study for five Smc1 and Smc2 strains, respectively, fully support their separate species status from a geno-taxonomic perspective. Given the recognized importance of gene gain and loss processes in bacterial speciation and ecological specialization (Richards et al, 2014 ; Caputo et al, 2015 ; Shapiro and Polz, 2015 ; Jeukens et al, 2017 ), as reported also in plants (Gordon et al, 2017 ), we think that the evidence gained from pan-genome phylogenies is particularly informative for microbial geno-taxonomic investigations. They should be used to validate the groupings obtained by the classical gANI cutoff-based species delimitation procedure (Konstantinidis and Tiedje, 2005 ; Goris et al, 2007 ; Richter and Rosselló-Móra, 2009 ) that dominates current geno-taxonomic research.…”
Section: Discussionmentioning
confidence: 92%
“…They should be used to validate the groupings obtained by the classical gANI cutoff-based species delimitation procedure (Konstantinidis and Tiedje, 2005 ; Goris et al, 2007 ; Richter and Rosselló-Móra, 2009 ) that dominates current geno-taxonomic research. It is well documented that pan-genome-based groupings tend to better reflect ecologically relevant phenotypic differences between groups (Lukjancenko et al, 2010 ; Caputo et al, 2015 ; Jeukens et al, 2017 ). We recommend that future geno-taxonomic studies search for a consensus of the complementary views of genomic diversity provided by OGRIs, core- and pan-genome phylogenies, as performed herein.…”
Section: Discussionmentioning
confidence: 99%
“…according to: i) VITEK ® MS microbiological testing ( n =12), ii) API 20 NE phenotypic testing ( n =85); iii) ARDRA ( n =13), and iv) WGS ( n =5) (Table S2). Among the Australian strains, two were previously identified as A. ruhlandii (QLDACH007 and QLDACH010) and two as A. xylosoxidans (QLDACH001 and AUS488) according to WGS (35, 36), one (QLDACH016) was a novel Achromobacter sp. according to WGS (36), and 110 were allocated as Achromobacter sp.…”
Section: Methodsmentioning
confidence: 99%